Validating an Automated Nucleic Acid Extraction Device for Omics in Space Using Whole Cell Microbial Reference Standards - Urbaniak, Camilla; Wong, Season; Tighe, Scott; Arumugam, Arunkumar; Liu, Bo; Parker, Ceth W.; Wood, Jason M.; Singh, Nitin K.; Skorupa, Dana J.; Peyton, Brent M.; Jenson, Ryan; Karouia, Fathi; et al. (Frontiers in Microbiology, 2020)
NASA has made great strides in the past five years to develop a suite of instruments for the International Space Station in order to perform molecular biology in space. However, a key piece of equipment that has been lacking is an instrument that can extract nucleic acids from an array of complex human and environmental samples. The Omics in Space team has developed the µTitan (simulated micro(µ) gravity tested instrument for automated nucleic acid) system capable of automated, streamlined, nucleic acid extraction that is adapted for use under microgravity. The µTitan system was validated using a whole cell microbial reference (WCMR) standard comprised of nine bacteria titrated at concentrations that would challenge the performance of the instrument, as well as resolve detection limits for isolating DNA. Quantitative assessment of system performance was measured by comparing instrument input challenge dose vs recovery by Qubit spectrofluorometry, qPCR, Bioanalyzer, and Next Generation Sequencing. Overall, results indicate that the µTitan system performs equal to or greater than a similar commercially available, earth-based, automated nucleic acid extraction device. The µTitan system was also tested in Yellowstone National Park (YNP) with the WCMR, to mimic a remote setting, with limited resources. The performance of the device at YNP was comparable to that in a laboratory setting. Such a portable, field-deployable, nucleic extraction system will be valuable for environmental microbiology, as well as health care diagnostics in preventing microbial diseases.